A Novel Surgical Approach to Lipomatous Tumours of the Deltoid Region. (22nd February 2010) - Al Absi, Emad; Karim, Tamanna; Colterjohn, Nigel; Ghert, Michelle
Abstract : Resection of large lipomatous tumours in the subdeltoid region remains technically challenging due to the risk of injury to the axillary neurovascular bundle. We describe a novel deltoid release and reinsertion technique for resection of large lipomatous tumours of the sub-deltoid region and report the functional and oncologic outcomes of six patients who underwent this procedure. Three cases were diagnosed histologically as atypical lipoma and three cases were diagnosed as lipoma. There was one local recurrence in a case of an atypical lipoma. Rotator cuff function was comparable to that of the contralateral side in all cases and the average Constant Score adopted by the European Shoulder and Elbow Society was 84 (range 81 to 92) out of 100. We conclude that patients with large sub-deltoid lipomatous tumours who undergo resection through a previously undescribed deltoid release and reinsertion technique have excellent functional outcome with a low risk for recurrence.